2019
DOI: 10.2217/nnm-2019-0231
|View full text |Cite
|
Sign up to set email alerts
|

ZnO Nanocrystals Shuttled By Extracellular Vesicles As Effective Trojan nano-horses Against Cancer Cells

Abstract: Aim: The effective application of nanoparticles in cancer theranostics is jeopardized by their aggregation in biological media, rapid degradation and clearance. The design of biomimetic nanoconstructs with enhanced colloidal stability and non-immunogenicity is therefore essential. We propose naturally stable cell-derived extracellular vesicles to encapsulate zinc oxide (ZnO) nanocrystals as efficacious nanodrugs, to obtain highly biomimetic and stable Trojan nano-horses (TNHs). Materials & methods: Couplin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 42 publications
(67 reference statements)
2
37
0
Order By: Relevance
“…A different distribution of treatments and number of shots could also be tested in order to maximize the synergy. Since the ZnO specific toxicity toward cancer cells is reported in the literature (Racca et al, 2018;Dumontel et al, 2019), additional tests with ZnO NCs and SW on healthy cells could be performed to confirm the selectivity of the proposed anticancer approach before to proceed with in vivo investigations.…”
Section: Future Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…A different distribution of treatments and number of shots could also be tested in order to maximize the synergy. Since the ZnO specific toxicity toward cancer cells is reported in the literature (Racca et al, 2018;Dumontel et al, 2019), additional tests with ZnO NCs and SW on healthy cells could be performed to confirm the selectivity of the proposed anticancer approach before to proceed with in vivo investigations.…”
Section: Future Overviewmentioning
confidence: 99%
“…An additional enhancement could be generated by improving the colloidal dispersibility of ZnO NCs (Dumontel et al, 2019;Limongi et al, 2019). These interesting features could be successfully exploited for a future application of ZnO NCs and SW in in vivo investigations and clinic.…”
Section: Future Overviewmentioning
confidence: 99%
“…They demonstrated that the coated MOF NPs were taken up within HeLa cells, enabling delivery of the anticancer drug suberoyl bishydroxamic acid. Dumontel et al coated zinc oxide nanocrystals (ZnO NCs) with EVs derived from KB (CCL17) cancer cells 37 . They evaluated various parameters for encapsulation within EVs, including the coupling temperature and time, mixing method, type of dispersing medium, and ratio between EVs and ZnO NCs.…”
Section: Extracellular Vesicles As Versatile Coatings For Nanoparticlesmentioning
confidence: 99%
“…A new nanoconstruct exploits the peculiar features of zinc oxide NPs (ZnO NPs) to treat cancer without the addition of drugs. Zinc oxide NPs encapsulated inside the EVs can be efficiently internalized by cancer cells causing their apoptosis [122]. A summary of cargo-loaded EVs with the related bibliographic references is provided in Table 2.…”
Section: Loading Nanotechnological Modification Into Evsmentioning
confidence: 99%